2021
DOI: 10.24841/fa.v30i1.542
|View full text |Cite
|
Sign up to set email alerts
|

Plantas Usadas Para Combatir La Pandemia Del Covid-19 en Una Comunidad Indígena Urarina Del Departamento De Loreto, Perú

Abstract: EEl artículo presenta las plantas usadas para combatir la pandemia del COVID-19 en una comunidad del pueblo indígena urarina, en la región Loreto, Perú. Se realizaron entrevistas semi estructuradas a promotores de salud, sabios, sabias, dirigentes y docentes de la comunidad durante la primera y segunda ola de la pandemia, de mayo del 2020 a junio del 2021. Al no poderse realizar viajes a la comunidad durante la primera ola de contagios, las entrevistas fueron realizadas vía telefónica o a través de aplicacione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
2
0
2
Order By: Relevance
“…Studies in the Peruvian Amazon have documented the use of medicinal plants by other Indigenous groups during the COVID-19 pandemic (16)(17)(18). For example, a study among the Urarina of Loreto reported on the use of plants for preventing or combating COVID-19 symptoms or to heal or strengthen the spirit against COVID-19 and other diseases (18).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the Peruvian Amazon have documented the use of medicinal plants by other Indigenous groups during the COVID-19 pandemic (16)(17)(18). For example, a study among the Urarina of Loreto reported on the use of plants for preventing or combating COVID-19 symptoms or to heal or strengthen the spirit against COVID-19 and other diseases (18).…”
Section: Discussionmentioning
confidence: 99%
“…The disruption of ethnographic fieldwork that seeks to investigate a specific social group’s ontological realities utterly conceals ecologically grounded relationships. It is worth remarking that, like most native Amazonians (see, e.g., for the Awajún ( Cárdenas Palacios & Reymundo Dámaso, 2021 ); for the Urarina ( Del Aguila Villacorta et al, 2021 ); for the Kichwa ( Oikonomakis, 2020 )), the Shuar are dealing with the pandemic through the aid of the vegetal world. As some informants told me, it seems that certain plants play a crucial role in curing coronavirus infection.…”
Section: Obfuscated Multispecies Assemblagesmentioning
confidence: 99%
“…La pandemia ha representado un gran desafío, y frente a ello se ha corroborado la vigencia de los prácticas tradicionales respecto al uso de plantas medicinales 16 , las cuales fueron efectivas en la disminución de los síntomas generados en el sistema respiratorio a causa de la COVID-19 17,10 , así como en la prevención de la misma 16 . Además, de ser usadas para prevenir y tratar, también sirvieron en la sanación y fortalecimiento del espíritu frente a la COVID-19 15 .…”
unclassified
“…De este modo, plantas como el ajo, jengibre, eucalipto, la cebolla, manzanilla y borraja fueron usadas para prevenir y tratar síntomas de la COVID-19, por sus propiedades antibacterianas, antivirales, antiinflamatorias, expectorantes, antipiréticas y antitusígenas 10,12,[15][16][17][18][19][20][21][22] , las cuales se administraron según la manifestación de los síntomas, el clima y la constitución corporal de la persona 23 .…”
unclassified